Studi Fenomenologi Peran Tim Pendamping Keluarga dalam Percepatan Penurunan Stunting di Daerah Pesisir Kabupaten Sumenep - Yulia Wardita; Sri Yunita Suraida Salat; Dian Permatasari; Nurul Khalifah (Wiraraja Medika : Jurnal Kesehatan, 2026)
Stunting remains a public health problem in the coastal areas of Sumenep Regency. This study aimed to explore the role of the Family Assistance Team (Tim Pendamping Keluarga/TPK) in accelerating stunting reduction in Dungkek District. The study employed a qualitative method with a phenomenological approach. A total of 17 informants were purposively selected, consisting of midwives, PKK cadres, family planning cadres, prospective brides and grooms, pregnant women, postpartum mothers, mothers of toddlers, community leaders, and the head of family planning services. Data were collected through in-depth interviews, observation, and documentation, and analyzed using thematic analysis. The findings revealed that TPK plays a role in nutrition and health education, assistance for families at risk of stunting, monitoring child growth and development, and facilitating access to health services. However, the implementation of these roles still faces challenges, including limited resources, low community participation, and parenting-related factors. This study indicates that TPK has a strategic role in supporting the acceleration of stunting reduction in coastal areas through strengthening family education and facilitating access to health services. These findings provide a basis for strengthening community-based TPK programs in coastal areas through enhancing cadre capacity, reinforcing cross-sectoral coordination, and optimizing community empowerment to ensure more effective and sustainable interventions.